Effects of Psychotherapy on Quality of Life in End-stage Renal Disease Patients: A Systematic Review with Meta-analysis - Phang, Kelly; Anis A Lliya, Abdul Latif *; Lee, Kai Wei; Ching, Siew Mooi; Ooi, Pei Boon * (Oman Medical Specialty Board, 2022)
Objectives: Patients with end-stage renal disease (ESRD) are known to experience poorer quality of life (QoL). The present study aimed to evaluate the effects of psychotherapy on QoL among patients with ESRD.